CXCL5 signaling is a shared pathway of neuroinflammation and blood–brain barrier injury contributing to white matter injury in the immature brain. Issue 1 (December 2016) - Wang, Lin-Yu; Tu, Yi-Fang; Lin, Yung-Chieh; Huang, Chao-Ching
Abstract Background In very preterm infants, white matter injury is a prominent brain injury, and hypoxic ischemia (HI) and infection are the two primary pathogenic factors of this injury. Microglia and microvascular endothelial cells closely interact; therefore, a common signaling pathway may cause neuroinflammation and blood–brain barrier (BBB) damage after injury to the immature brain. CXC chemokine ligand 5 (CXCL5) is produced in inflammatory and endothelial cells by various organs in response to insults. CXCL5 levels markedly increased in the amniotic cavity in response to intrauterine infection and preterm birth in clinical studies. The objective of this study is to determine whether CXCL5 signaling is a shared pathway of neuroinflammation and BBB injury that contributes to white matter injury in the immature brain. Methods Postpartum day 2 (P2) rat pups received lipopolysaccharide (LPS) followed by 90-min HI. Immunohistochemical analyses were performed to determine microglial activation, neutrophil infiltration, BBB damage, and myelin basic protein and glial fibrillary acidic protein expression. Immunofluorescence experiments were performed to determine the cellular distribution of CXCL5. Pharmacological tests were performed to inhibit or enhance CXCL5 activity. Results On P2, predominant increases in microglial activation and BBB damage were observed 24 h after LPS-sensitized HI induction, and white matter injury (decreased myelination and increased astrogliosis) was observed on P12 compared with controls. Immunohistochemical analyses revealed increased CXCL5 expression in the white matter 6 and 24 h after insult. Immunofluorescence experiments revealed upregulated CXCL5 expression in the activated microglia and endothelial cells 24 h after insult. CXCL5 inhibition by SB225002, a selective nonpeptide inhibitor of CXCR2, significantly attenuated microglial activation and BBB damage, increased myelination, and reduced astrogliosis in the white matter after LPS-sensitized HI. In addition, CXCL5-sensitized HI or CXCL5 alone significantly induced BBB damage and white matter injury in association with different neuroinflammation mechanisms. CXCL5-sensitized HI-induced microglial activation and neutrophil infiltration, whereas CXCL5 alone predominately caused neutrophil infiltration. Conclusions CXCL5 is a potential biomarker for white matter injury in preterm infants. Pharmacological blockade of CXCL5 signaling that attenuates dysregulated neuroinflammation can be used a therapeutic strategy against white matter injury in the immature brain.